2012
DOI: 10.1128/jvi.00018-12
|View full text |Cite
|
Sign up to set email alerts
|

Helper Virus-Independent Transcription and Multimerization of a Satellite RNA Associated with Cucumber Mosaic Virus

Abstract: Satellite RNAs are the smallest infectious agents whose replication is thought to be completely dependent on their helper virus (HV). Here we report that, when expressed autonomously in the absence of HV, a variant of satellite RNA (satRNA) associated with Cucumber mosaic virus strain Q (Q-satRNA) has a propensity to localize in the nucleus and be transcribed, generating genomic and antigenomic multimeric forms. The involvement of the nuclear phase of Q-satRNA was further confirmed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…We previously demonstrated that Q-satRNA has a propensity to enter the nucleus in the presence and absence of its HV (13). To shed more light on the subcellular compartmentalization of Q-satRNA, we wanted to analyze the distribution of Q-satRNA in the presence and absence of HV during early stages of replication.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that Q-satRNA has a propensity to enter the nucleus in the presence and absence of its HV (13). To shed more light on the subcellular compartmentalization of Q-satRNA, we wanted to analyze the distribution of Q-satRNA in the presence and absence of HV during early stages of replication.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we performed a bacteriophage MS2-coat protein (MS2-CP) RNA tagging assay that allows visualizing the subcellular location of Q-satRNA in living cells (31) in wild-type (wt) and BRP1-suppressed transgenic lines of N. benthamiana. Briefly, a 23-nt MS2-CP binding site was engineered into stem loop C of Q-satRNA by the double joint PCR method as described previously (13). This approach allows specific interaction between RNA molecules bearing binding sites and RNAbinding proteins (such as MS2-CP), permitting the visualization of subcellular locations of RNA molecules in living cells when these molecules are coexpressed with an RNA-binding protein fused with GFP (such as MS2-CP-GFP).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations